SYNTHESIS AND IDENTIFICATION OF SCHIFF BASES AND BILOGICAL ACTIVITY NEW STUDY - Essa, Hameed; Kandil, Farouk; Falah, Ahmad (Iraqi Journal of Science, 2024)
In this work we focused on the synthesis of new Open Schiff bases which wereprepared by condensation of salicylaldehyde with both 4,4’-diaminodiphenylmethane,4,4’-diamino diphenyl sulphide,and by condensation of O-vanilin withdiethyl ester of terephthalic acid respectively.Also new macrocyclic Schiff Baseswere prepared by condensation of 1,6-bis(2-formylphenyl)hexane withthiocarbohydrazid.The Schiff bases were checked by different spectral technique(LC-MS, 1H-NMR, IR). The work was extended to study the effect of the preparedcompounds on four different bacteria in order to test there biological activity